Aqueous undercoating material

A water-based undercoating material with a specific synthetic resin emulsion and alkoxysilane compounds addresses adhesion and weather resistance issues, ensuring robust performance against blistering and cracking.

JP2024176155APending Publication Date: 2024-12-19BEKKU KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023094461
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-08
Publication Date
2024-12-19

AI Technical Summary

Technical Problem

Water-based undercoating materials often suffer from inferior adhesion and insufficient weather resistance, particularly when used with highly decorative top coat materials, leading to issues like blistering and cracking.

Method used

A water-based undercoating material containing a synthetic resin emulsion with specific monomer components, including (meth)acrylic acid alkyl esters and alkoxysilane compounds, with a glass transition temperature of 15°C or less, in a specific mass ratio, to enhance adhesion and weather resistance.

Benefits of technology

The material exhibits excellent adhesion, blistering resistance, and cracking resistance, effectively preventing defects in the top coat material, especially under varying environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176155000001
    Figure 2024176155000001
  • Figure 2024176155000002
    Figure 2024176155000002
Patent Text Reader

Abstract

To provide an aqueous undercoating material excellent in weather resistance and capable of sufficiently exhibiting performance such as adhesion, swelling resistance, and crack resistance.SOLUTION: An aqueous undercoating material contains a synthetic resin emulsion and a pigment. The synthetic resin emulsion contains (a) an alkyl (meth)acrylate having an alicyclic hydrocarbon group and (b) an alkoxysilane compound as components constituting a synthetic resin. The alkoxysilane compound (b) is contained in an amount of 0.01-7 mass% in constituent components of the synthetic resin. The glass transition temperature of the synthetic resin is 15°C or lower.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel water-based primer. [Background technology]

[0002] Buildings, civil engineering structures, etc. are painted to protect their framework and improve their appearance. In such painting, a primer is usually applied first, followed by a topcoat. Such primers have traditionally been solvent-based, but recently, water-based primers have been adopted in consideration of the environment, safety, etc. (For example, see Patent Document 1).

[0003] However, water-based undercoats may have inferior adhesion compared to solvent-based undercoats. In particular, sufficient adhesion may not be obtained depending on the painting environment. In addition, when applying highly design-oriented paints (e.g., multicolored paints, glitter paints, aggregate-based paints, colored transparent paints, etc.) as topcoats, paint finishes that make use of the color tone and texture of the undercoat are used, but sufficient weather resistance is not obtained, and there is a risk of reduced adhesion with the topcoat, or swelling or cracking of the paint film. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2004-122052 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in consideration of such problems, and aims to provide a water-based primer that has excellent weather resistance and can fully exhibit performance such as adhesion, blister resistance, and crack resistance. [Means for solving the problem]

[0006] As a result of extensive research into these problems, the inventors discovered an aqueous primer material that contains a pigment and a synthetic resin emulsion that contains specific monomer components in specific mass ratios as constituent components, and thus completed the present invention.

[0007] That is, the present invention has the following features. 1. A water-based primer containing a synthetic resin emulsion and a pigment, The synthetic resin emulsion contains the following components constituting the synthetic resin: (a) a (meth)acrylic acid alkyl ester having an alicyclic hydrocarbon group, and (b) an alkoxysilane compound, Including, The synthetic resin contains the alkoxysilane compound (b) in an amount of 0.01 to 7% by mass, A water-based primer material characterized in that the synthetic resin has a glass transition temperature of 15°C or lower. 2.Furthermore, the synthetic resin emulsion contains the following components as constituents of the synthetic resin: (c) containing a (meth)acrylic acid alkyl ester having an alkyl main chain having 1 to 2 carbon atoms in the alkyl portion, The water-based primer according to claim 1, characterized in that the mass ratio [(a) / (c)] of the (a) (meth)acrylic acid alkyl ester having an alicyclic hydrocarbon group to the (c) (meth)acrylic acid alkyl ester having an alkyl main chain with 1 to 2 carbon atoms in the alkyl portion is 100 / 0 to 1 / 99. Effect of the Invention

[0008] The water-based primer of the present invention has excellent weather resistance and can fully exhibit properties such as adhesion, blister resistance, and crack resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention relates to a water-based primer comprising a synthetic resin emulsion and a pigment.

[0010] The synthetic resin emulsion of the present invention contains, as a component constituting the synthetic resin, (a) a (meth)acrylic acid alkyl ester having an alicyclic hydrocarbon group, and (b) an alkoxysilane compound, The present invention is characterized by comprising: In the present invention, alkyl acrylates and alkyl methacrylates are collectively referred to as alkyl (meth)acrylates.

[0011] Furthermore, the synthetic resin is characterized in that its glass transition temperature (hereinafter simply referred to as "Tg") is 15°C or lower (more preferably, from -50°C to 13°C, and even more preferably, from -30°C to 12°C). This allows the performance such as weather resistance, adhesion, blister resistance, and crack resistance to be fully exhibited. The glass transition temperature can be calculated by the Fox formula. However, the calculation of the glass transition temperature of the present invention excludes (b) the alkoxysilane compound.

[0012] (a) Examples of (meth)acrylic acid alkyl esters having an alicyclic hydrocarbon group (hereinafter also referred to as "component (a)") include cyclohexyl acrylate, cyclohexyl methacrylate, isobornyl acrylate, isobornyl methacrylate, dicyclopentanyl acrylate, dicyclopentanyl methacrylate, dicyclopentenyl acrylate, and the like. These can be used alone or in combination of two or more. Among these, cyclohexyl methacrylate is particularly preferred.

[0013] In the present invention, the synthetic resin contains the component (a) in an amount of preferably 0.1 to 40% by mass (more preferably 0.5 to 35% by mass, and even more preferably 1 to 30% by mass), thereby improving weather resistance.

[0014] Examples of the (b) alkoxysilane compound (hereinafter also referred to as "component (b)") include alkoxysilane compounds having a polymerizable unsaturated double bond, such as γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltriisopropoxysilane; Alkoxysilane compounds having a glycidyl group, such as γ-glycidoxymethacryloxypropyltrimethoxysilane, γ-glycidoxymethacryloxypropylmethyldimethoxysilane, γ-glycidoxymethacryloxypropyltriethoxysilane, γ-glycidoxymethacryloxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; Alkoxysilane compounds having an amino group, such as N-2(aminoethyl)3-aminopropyltrimethoxysilane, N-2(aminoethyl)3-aminopropylmethyldimethoxysilane, N-2(aminoethyl)3-aminopropyltriethoxysilane, N-2(aminoethyl)3-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane; alkoxysilane compounds having a mercapto group, such as γ-mercaptopropyltrimethoxysilane; Tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane, tetra-i-propoxysilane, tetra-n-butoxysilane, tetra-i-butoxysilane, tetra-t-butoxysilane, methyltrimethoxysilane, methyltriethoxysilane, methyltrippropoxysilane, methyltributoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltrippropoxysilane, ethyltributoxysilane, propyltrimethoxysilane, propyltriethoxysilane, propyltrippropoxysilane, propyltributoxysilane, butyltrimethoxysilane, butyltriethoxysilane, butyltrippropoxy Examples of the alkoxysilane include silane, butyl tributoxy silane, dimethyl dimethoxy silane, dimethyl diethoxy silane, dimethyl dipropoxy silane, dimethyl dibutoxy silane, diethyl dimethyl silane, diethyl diethoxy silane, diethyl dipropoxy silane, diethyl dibutoxy silane, cyclohexyl methyl dimethoxy silane, γ-chloropropyl trimethoxy silane, and γ-anilinopropyl trimethoxy silane, and alkoxy silane modified products in which at least a part of the alkoxyl groups of these alkoxy silanes is modified with a polyoxyalkylene group-containing compound, an amino group-containing compound, a fluorine-containing compound, or the like. These can be used alone or in combination. Among these, it is particularly preferable to use an alkoxy silane compound having a polymerizable unsaturated double bond, an alkoxy silane compound having a glycidyl group, or an alkoxy silane compound having an amino group.

[0015] In the present invention, the synthetic resin contains preferably 0.01 to 7% by mass (more preferably 0.02 to 5% by mass, even more preferably 0.03 to 3% by mass, and particularly preferably 0.05 to 2% by mass) of component (b). This increases the strength of the coating film, and can improve blister resistance and crack resistance, while also being advantageous in terms of adhesion. If the content of component (b) exceeds the upper limit range, the coating film may become too hard, and crack resistance and the like may decrease. If the content does not meet the lower limit range, the above effects may be insufficient.

[0016] In the present invention, in addition to the above components (a) and (b), it is preferable to include (c) an alkyl (meth)acrylate ester having an alkyl main chain with 1 to 2 carbon atoms in the alkyl portion (hereinafter also referred to as "component (c)"). This can further increase the coating strength. As component (c), a compound having an alkyl portion that is a linear or branched alkyl group (excluding component (a) above) and having a main chain (longest carbon straight chain) with 1 to 2 carbon atoms can be used, and examples of such compounds include methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, and t-butyl (meth)acrylate. These compounds can be used alone or in combination of two or more. Among these, methyl (meth)acrylate is particularly preferred.

[0017] In the present invention, the synthetic resin components can contain preferably 0 to 50% by mass (more preferably 1 to 45% by mass, and even more preferably 2 to 40% by mass) of the component (c). In addition, in the present invention, the mass ratio [(a) / (c)] of the above-mentioned component (a) and the above-mentioned component (c) in the synthetic resin components is preferably 100 / 0 to 1 / 99 (more preferably 99 / 1 to 5 / 95, and even more preferably 90 / 10 to 10 / 90). When such conditions are met, it is even more preferable in that a coating film having weather resistance, adhesion, crack resistance, etc. can be formed. Furthermore, the adhesion with the topcoat material, especially at low temperatures, can be fully demonstrated. As a result, the occurrence of defects such as swelling, cracking, and peeling in the topcoat material can be suppressed.

[0018] Furthermore, in addition to the above components (a), (b), and (c), it is preferable to include (d) an alkyl (meth)acrylate having an alkyl main chain with 3 or more carbon atoms (hereinafter also referred to as "component (d)") (excluding component (a)). The alkyl portion of the alkyl (meth)acrylate having an alkyl main chain with 3 or more carbon atoms is a linear or branched alkyl group (excluding cyclic groups), and the main chain (the longest carbon linear chain) has 3 or more carbon atoms. The alkyl portion of component (d) has an alkyl main chain with 3 or more carbon atoms. As long as the alkyl portion of component (d) has such an alkyl main chain, it may have various side chains (for example, an alkyl group having fewer carbon atoms than the alkyl main chain). As component (d), an alkyl (meth)acrylate that satisfies these conditions can be used, for example, (meth)acrylic acid alkyl esters (d1) having an alkyl main chain having 3 to 5 carbon atoms, such as n-propyl (meth)acrylate, isobutyl (meth)acrylate, 1-ethylpropyl (meth)acrylate, t-pentyl (meth)acrylate, neopentyl (meth)acrylate, n-butyl (meth)acrylate, 2-methylbutyl (meth)acrylate, isopentyl (meth)acrylate, 3-methylbutyl (meth)acrylate, 2-ethylbutyl (meth)acrylate, n-pentyl (meth)acrylate, 2-methylpentyl (meth)acrylate, and 4-methylpentyl (meth)acrylate; Examples of the alkyl (meth)acrylates (d2) include alkyl (meth)acrylates having an alkyl main chain having 6 or more carbon atoms, such as n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-heptyl (meth)acrylate, isooctyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, n-decyl (meth)acrylate, n-undecyl (meth)acrylate, and n-lauryl (meth)acrylate. These can be used alone or in combination of two or more.

[0019] In the present invention, the synthetic resin contains preferably 10 to 85% by mass (more preferably 20 to 80% by mass) of component (d), allowing the effects of the present invention to be fully exhibited.

[0020] When the (d) component contains the (d1) component and the (d2) component, in addition to the elongation and adhesion, it is advantageous in terms of strength, and can further improve the performance of preventing blistering, peeling, cracking, etc. The mass ratio of the (d1) component to the (d2) component [(d1) / (d2)] is preferably 10 / 90 to 80 / 20 (more preferably 20 / 80 to 70 / 30). In such a case, the above-mentioned effects can be further improved.

[0021] In the present invention, in addition to the above, other compounds having polymerizable unsaturated double bonds can be included. Examples of such compounds include amide group-containing monomers, carbonyl group-containing monomers, carboxyl group-containing monomers, epoxy group-containing monomers, amino group-containing monomers, hydroxyl group-containing monomers, aromatic group-containing monomers, nitrile group-containing monomers, halogenated vinylidene monomers, ethylene, propylene, isoprene, butadiene, vinyl ether, vinyl ketone, etc. These can be used alone or in combination of two or more.

[0022] specifically, Examples of the amide group-containing monomer include maleic acid amide, (meth)acrylamide, N-monoalkyl (meth)acrylamide, N,N-dialkyl (meth)acrylamide, 2-(dimethylamino)ethyl (methacrylate), N-[3-(dimethylamino)propyl] (meth)acrylamide, and vinylamide. Examples of the carbonyl group-containing monomer include acrolein, diacetone (meth)acrylamide, vinyl methyl ketone, vinyl ethyl ketone, and vinyl butyl ketone. Examples of the carboxyl group-containing monomer include (meth)acrylic acid, crotonic acid, maleic acid, itaconic acid, fumaric acid, isocrotonic acid, and salicylic acid. Examples of epoxy group-containing monomers include glycidyl (meth)acrylate, diglycidyl fumarate, 3,4-epoxycyclohexyl (meth)acrylate, 3,4-epoxyvinylcyclohexane, allyl glycidyl ether, ε-caprolactone-modified glycidyl (meth)acrylate, and β-methylglycidyl (meth)acrylate. Examples of amino group-containing monomers include aminomethyl acrylate, aminoethyl acrylate, aminopropyl (meth)acrylate, amino-n-butyl (meth)acrylate, butylvinylbenzylamine, vinylphenylamine, p-aminostyrene, N-methylaminoethyl (meth)acrylate, and Nt-butylaminoethyl (meth)acrylate. Examples of hydroxyl group-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 5-hydroxyamyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, and 10-hydroxydecyl (meth)acrylate. Examples of aromatic group-containing monomers include styrene-based monomers such as styrene, 2-methylstyrene, vinyltoluene, ethylvinylbenzene, vinylnaphthalene, and chlorostyrene; aromatic group-containing (meth)acrylates such as phenyl(meth)acrylate, benzyl(meth)acrylate, and phenoxyethyl(meth)acrylate; Examples of nitrile group-containing monomers include (meth)acrylonitrile, vinylidene cyanide, and α-cyanoethyl (meth)acrylate. Examples of vinylidene halide monomers include vinylidene fluoride, etc. These can be used alone or in combination of two or more. If necessary, a crosslinking agent such as ethylene glycol diacrylate, ethylene glycol dimethacrylate, allyl acrylate, allyl methacrylate, divinylbenzene, or trimethylolpropane triacrylate may be used.

[0023] The synthetic resin of the present invention is a polymer obtained by polymerizing a monomer group obtained by appropriately mixing the above (a) (meth)acrylic acid alkyl ester having an alicyclic hydrocarbon group, the above (b) alkoxysilane compound, and the above other polymerizable unsaturated monomers. The polymerization method may be a known method, and in addition to normal emulsion polymerization, soap-free emulsion polymerization, feed emulsion polymerization, seed emulsion polymerization, etc. may also be used. During polymerization, for example, an emulsifier, an initiator, a dispersant, a polymerization inhibitor, a polymerization retarder, a buffer, a chain transfer agent, a pH adjuster, etc. may be used.

[0024] In particular, it is preferable that the synthetic resin emulsion is obtained by emulsion polymerization. The emulsion polymerization may be performed in one stage, or may be a multi-stage emulsion polymerization performed in two or more stages. When it is performed in one stage, a single-layer structure type synthetic resin emulsion can be obtained. When it is performed in two or more stages, the composition and content of the above-mentioned (a) component, the above-mentioned (b) component, the above-mentioned (c) component, the above-mentioned (d) component, etc. can be adjusted in each stage, and a multi-layer structure type synthetic resin emulsion (for example, a core-shell type synthetic resin emulsion, etc.) can be obtained. In the case of a single-layer structure type synthetic resin emulsion, it is preferable that the mass ratio of the above-mentioned (a) component to the above-mentioned (c) component satisfies (a)>(c), and further, the mass ratio of the above-mentioned (a) component to the above-mentioned (c) component [(a) / (c)] can be preferably 100 / 0 to 55 / 45 (more preferably 99 / 1 to 55 / 45, even more preferably 97 / 3 to 60 / 40, and particularly preferably 95 / 5 to 65 / 35). In the case of a multi-layered synthetic resin emulsion, in the outermost layer, the mass ratio of the above-mentioned (a) component to the above-mentioned (c) component preferably satisfies (a)>(c), and further the mass ratio of the above-mentioned (a) component to the above-mentioned (c) component [(a) / (c)] can be preferably 100 / 0 to 55 / 45 (more preferably 100 / 0 to 60 / 40, even more preferably 100 / 0 to 65 / 35). In this case, it is even more preferable in that a coating film having weather resistance, adhesion, crack resistance, etc. can be formed. Furthermore, it is possible to fully exert adhesion with the topcoat material, especially adhesion at low temperatures. As a result, it is possible to suppress the occurrence of defects such as swelling, cracking, and peeling in the topcoat material.

[0025] As the emulsifier, various surfactants that can be used in emulsion polymerization can be used, and these may be reactive types (reactive surfactants) having polymerizable unsaturated double bonds. As the emulsifier, for example, anionic surfactants, nonionic surfactants, cationic surfactants, amphoteric surfactants, etc. can be used alone or in combination.

[0026] The average particle size of the synthetic resin emulsion (synthetic resin particles) is not particularly limited, but is preferably 300 nm or less (more preferably 20 to 250 nm, and even more preferably 30 to 200 nm). If the average particle size is within such a range, advantageous effects can be obtained in impregnation reinforcement, sealing properties, efflorescence resistance, whitening resistance, etc., and the effects of the present invention can be enhanced. The average particle size referred to here is a value measured by a dynamic light scattering method.

[0027] The water-based undercoat material of the present invention is characterized by containing a pigment in addition to the synthetic resin emulsion. For example, known pigments such as color pigments, extender pigments, and rust-preventive pigments can be used. The blending amount of the pigment is preferably 10 to 600 parts by mass (more preferably 15 to 500 parts by mass) per 100 parts by mass of the solid content of the synthetic resin emulsion. In such a case, the effect of the present invention can be fully exhibited.

[0028] Specifically, the color pigment may be a chromatic pigment, a white pigment, a black pigment, or the like. Among these, the chromatic pigment is a pigment that exhibits a chromatic color such as yellow, orange, red, green, blue, or purple. Examples of such chromatic pigments include inorganic pigments such as ferric oxide, ferric oxide hydrate, ultramarine, cobalt blue, and cobalt green, and organic pigments such as azo, naphthol, pyrazolone, anthraquinone, perylene, quinacridone, disazo, isoindolinone, benzimidazole, phthalocyanine, and quinophthalone. On the other hand, the white pigment is a pigment that exhibits white color, and examples thereof include titanium oxide, zinc oxide, and aluminum oxide. The black pigment is a pigment that exhibits a black color, and examples thereof include inorganic pigments such as iron black, iron-manganese composite oxide, iron-copper-manganese composite oxide, iron-chromium-cobalt composite oxide, copper-chromium composite oxide, copper-manganese-chromium composite oxide, and carbon black. These can be used alone or in combination of two or more. The surface of the pigment may be treated in some way. The average particle size of the color pigment is preferably 1 μm or less, and more preferably 0.01 to 0.9 μm. The average particle size of the color pigment is a value measured by a laser diffraction particle size distribution measuring device.

[0029] The blending amount of the color pigment is preferably 1 to 150 parts by mass (more preferably 5 to 100 parts by mass) per 100 parts by mass of the solid content of the synthetic resin emulsion. If the color pigment is in such a ratio, the coating material can be colored in a desired color, and the hiding power, aesthetics, etc. can be improved.

[0030] Examples of extender pigments include heavy calcium carbonate, light calcium carbonate, clay, kaolin, talc, barium carbonate, white carbon, diatomaceous earth, kansui stone, china clay, barite powder, barium sulfate, precipitated barium sulfate, barium carbonate, magnesium carbonate, silica powder, silica sand, silica stone powder, quartz powder, hydrous silicic acid powder, aluminum hydroxide, resin beads, glass beads, hollow ceramic beads, hollow resin beads, etc. These can be used alone or in combination of two or more. The average particle size of the body pigment is preferably 0.1 to 100 μm (preferably 1 to 80 μm). The average particle size of the body pigment is a value measured by a laser diffraction particle size distribution measuring device.

[0031] The amount of the extender pigment is preferably 1 to 500 parts by mass (more preferably 5 to 300 parts by mass, and even more preferably 10 to 200 parts by mass) per 100 parts by mass of the solid content of the synthetic resin emulsion. If the extender pigment is in such a ratio, it is advantageous for example in homogenizing the base surface, improving adhesion with the base and topcoat material, and improving the coating strength.

[0032] In addition, hollow particles such as hollow ceramic beads and hollow resin beads can be used as extender pigments to impart heat insulation to the formed coating film (undercoat layer). However, increasing the heat insulation performance of the undercoat material (undercoat layer) increases the thermal load on the topcoat layer formed on top of it, which may cause the coating film to swell or peel off. In contrast, the aqueous undercoat material of the present invention can sufficiently suppress the swelling, peeling, etc. of the coating film by using the above-mentioned synthetic resin emulsion. Although this mechanism of action is not limited, as described above, by containing the above-mentioned (b) component in the constituent components of the synthetic resin, the coating film strength is increased and sufficient adhesion with the topcoat layer is obtained, and as a result, it is presumed that swelling, peeling, etc. due to thermal load can be suppressed.

[0033] The aqueous coating material of the present invention can be obtained by mixing, as necessary, aggregates, fibers, pH adjusters, plasticizers, preservatives, antifungal agents, anti-algae agents, defoamers, leveling agents, coupling agents, dispersants, anti-settling agents, anti-sagging agents, thickeners (thixotropic adjusters), film-forming assistants, matting agents, adsorbents, crosslinking agents, catalysts, curing accelerators, adhesion agents, ultraviolet absorbers, light stabilizers, etc., either alone or in combination. Furthermore, viscosity, etc. can be adjusted by adding water as appropriate.

[0034] <Film formation method> The water-based undercoat material of the present invention can be preferably applied to a substrate such as a substrate or an old coating film. A specific application method is a coating formation method in which a undercoat material and a topcoat material are applied to a substrate in that order, and the water-based undercoat material of the present invention is used as the undercoat material. This provides excellent weather resistance and can fully exhibit performance such as adhesion, blister resistance, and crack resistance. In particular, the weather resistance, blister resistance, and discoloration of the topcoat material can be fully suppressed.

[0035] Examples of the base material for the above-mentioned foundation include concrete, mortar, slate board, calcium silicate board, ALC board, extrusion molded board, slate roofing tiles, cement roofing tiles, new roofing tiles, porcelain tiles, siding boards, metal, glass, wood, plywood, and the like.

[0036] The old coating film is a coating film that is applied on the above-mentioned substrate, and examples of such coating films include weather-resistant topcoat paints for architecture (JISK 5658:2010), weather-resistant paints for steel structures (JISK 5659:2021), glossy synthetic resin emulsion paints (JISK5660:2021), synthetic resin emulsion paints (JIS K5663:2021), synthetic resin emulsion pattern paints (JIS K5668:2021), multi-color pattern paints (JIS K5667:2003), acrylic resin-based non-aqueous dispersion paints (JIS K5670:2021), high solar reflectance paints for roofs (JIS K5675:2011), architectural coating waterproofing materials (JIS A6021:2022), architectural fireproof paints (JISK5661:1970), road marking paints (JIS Examples of coating films include those formed by JIS K5665:2016), lead- and chromium-free rust-preventive paint (JIS K5674:2008), building floor paint (JIS K5970:2008), architectural finishing coating material (JIS A6909:2021), and other stone-like finishing coating materials. The present invention can also be applied to fluororesin coating films, silicone resin coating films, and the like.

[0037] In the application of the water-based undercoat material of the present invention, various methods can be used, such as brush application, trowel application, roller application, spray application, etc. In addition, when applying in a factory, it is also possible to apply using a roll coater, flow coater, etc.

[0038] The amount of water-based undercoat applied is preferably 0.1 to 3 kg / m 2 (More preferably 0.2 to 2 kg / m 2 ). The number of applications may be appropriately set depending on the surface condition of the substrate, but is preferably 1 to 2 times. The drying time is preferably 1 hour to 1 week. The drying temperature is preferably -10°C to 50°C (more preferably -5°C to 40°C). The aqueous undercoat material of the present invention is preferably a room temperature curing type.

[0039] In the present invention, after the application and drying of the water-based undercoat material, a topcoat material can be applied. By applying a topcoat material, it is possible to protect the finished surface or improve the aesthetic appearance. As the topcoat material, those generally used for painting buildings can be used. As the resin component in the topcoat material, various resins can be used. Examples of the types of resin include vinyl acetate resin, polyester resin, alkyd resin, vinyl chloride resin, epoxy resin, acrylic resin, urethane resin, acrylic silicone resin, fluororesin, etc., or composite resins thereof. In addition, examples of the form of such resin components include water-soluble resin, water-dispersible resin (resin emulsion), solvent-soluble resin, solventless resin, non-water-dispersible resin, powdered resin, etc.

[0040] In the present invention, a water-based topcoat material containing a resin emulsion such as an acrylic resin, a urethane resin, an acrylic silicone resin, or a fluororesin is suitable, and a topcoat material containing an alkyl (meth)acrylate ester having a cyclic alkyl group as a resin component can also be used.

[0041] Such a topcoat material may contain various components other than the above-mentioned components, as long as the effect of the present invention is not significantly impaired. Examples of such components include thickeners, film-forming assistants, leveling agents, coupling agents, wetting agents, plasticizers, antifreeze agents, pH adjusters, coloring pigments, extender pigments, aggregates, preservatives, antifungal agents, antialgae agents, antibacterial agents, dispersants, antifoaming agents, adsorbents, fibers, crosslinking agents, ultraviolet absorbers, light stabilizers, antioxidants, low-pollution agents, hydrophilizing agents, water repellents, catalysts, solvents, and water. The topcoat material of the present invention can be manufactured by uniformly mixing the above-mentioned resin components and, if necessary, the above-mentioned various components by conventional methods. The form of the topcoat material can be, for example, a one-component type, a two-component type, or a multi-component type.

[0042] Specific topcoat materials include, for example, weather-resistant topcoat paint for architecture (JISK5658:2010), weather-resistant paint for steel structures (JISK5659:2021), glossy synthetic resin emulsion paint (JISK5660:2021), synthetic resin emulsion paint (JIS K5663:2021), synthetic resin emulsion pattern paint (JIS K5668:2021), multi-color pattern paint (JIS K5667:2003), acrylic resin non-aqueous dispersion paint (JIS K5670:2021), high solar reflectance paint for roofs (JIS K5675:2011), architectural coating waterproofing material (JIS A6021:2022), architectural fireproof paint (JISK5661:1970), road marking paint (JIS K5665:2016), lead- and chromium-free rust-preventive paint (JISK5674:2008), building floor paint (JISK5970:2008), architectural finishing coating material (JIS 6909:2021), other stone-like finishing coating materials, sandstone-like finishing coating materials, stone-like finish coating materials, diatomaceous finishing coating materials, special design finishing coating materials, clear paints, etc. can be used as topcoats. In the present invention, advantageous effects can be obtained when multicolored pattern paints, stone-like finishing coating materials, etc. are used as topcoats.

[0043] The method of applying the topcoat material is not particularly limited and can be applied by a known method, for example, brushing, troweling, spraying, roller coating, roll coater, flow coater, etc., and can be applied by various methods. That is, each topcoat material may be applied based on the normal process with the optimal coating specifications (number of coats, drying temperature, etc.) for each topcoat material. The drying temperature is preferably -10°C or higher and 50°C or lower, more preferably -5°C or higher and 40°C or lower. The coating formation method of the present invention is preferable as a room temperature curing type. EXAMPLES

[0044] The following examples and comparative examples will clarify the features of the present invention.

[0045] <Production of water-based undercoat materials> (Water-based primer 1~15) 200 parts by mass of synthetic resin emulsion (100 parts by mass of solids) were mixed and stirred by a standard method with 30 parts by mass of titanium oxide (average particle size: 0.3 μm), 50 parts by mass of heavy calcium carbonate (average particle size: 20 μm), 5 parts by mass of hollow resin beads (acrylic-acrylonitrile copolymer resin, average particle size 40 μm), 2 parts by mass of thickener, 2 parts by mass of dispersant, 3 parts by mass of defoamer, 18 parts by mass of ether-based solvent, and 20 parts by mass of water to obtain water-based primers 1 to 15. (Water-based primer 16~17) 200 parts by mass of synthetic resin emulsion (100 parts by mass of solids) were mixed and stirred in a standard manner with 30 parts by mass of titanium oxide (average particle size: 0.3 μm), 55 parts by mass of heavy calcium carbonate (average particle size: 20 μm), 2 parts by mass of thickener, 2 parts by mass of dispersant, 3 parts by mass of defoamer, 18 parts by mass of ether-based solvent, and 20 parts by mass of water to obtain water-based primers 16 to 17.

[0046] As the synthetic resin emulsion, an emulsion polymer (solid content: 50% by mass) having the components shown in Table 1 was used. The components of the synthetic resin shown in Table 1 are as follows: CHMA: Cyclohexyl methacrylate (Tg: 83℃) MMA: Methyl methacrylate (Tg: 105℃) n-BMA: n-butyl methacrylate (Tg: 20℃) 2EHA: 2-Ethylhexyl acrylate (Tg: -70℃) ·AA: Acrylic acid (Tg: 106℃) ·Si: γ-Methacryloxypropyltrimethoxysilane

[0047] [Table 1]

[0048] (Examples 1 to 13, Comparative Examples 1 to 4) The following evaluations were carried out using each of the obtained water-based primer materials.

[0049] <Preparation of test specimen (1)> Each water-based primer was applied at a rate of 1.2 kg / m to one side of a slate board (300 x 150 x 6 mm). 2 After drying for 3 hours, a topcoat (a water-based acrylic silicone resin paint corresponding to JIS K5660 glossy synthetic resin emulsion paint) was applied at a rate of 0.3 kg / m. 2 The test specimen (1) was prepared by painting the specimen with the above paint and curing it for 7 days. The painting and curing processes were all carried out under standard conditions (temperature 23°C, relative humidity 50%).

[0050] [Rating 1] For the specimen (1) obtained by the above method, an accelerated weather resistance test was carried out using an Eye Super UV Tester (manufactured by Iwasaki Electric Co., Ltd.) as an accelerated weather resistance tester, with one cycle consisting of 6 hours of light irradiation and 2 hours of condensation (total 8 hours), up to 60 cycles. At this time, the appearance changes of the surface of the specimen (the occurrence of defects such as swelling, peeling, and cracking) were observed at the end of the 20th cycle, the end of the 40th cycle, and the end of the 60th cycle. The evaluation criteria were as follows: Changes in appearance were evaluated on a four-point scale (A>B>C>D; poor) ranging from "A: no change" to "D: obvious defect was observed." The evaluation results are shown in Table 2. [Rating 2] The specimen (1) obtained by the above method was irradiated with an infrared lamp (output 250 W) from a distance of 60 cm for 8 hours, and then immersed in water at 23°C for 16 hours, for a total of 10 cycles, after which the appearance (the occurrence of defects such as swelling, peeling, and lifting) was visually observed. Evaluation was made on a four-level scale (excellent; A>B>C>D; poor) from "A: no change" to "D: defects clearly observed." The evaluation results are shown in Table 2.

[0051] [Rating 3] The specimen (1) obtained by the above method was immersed in water for 4 days, and then the adhesion was evaluated by the cross-cut tape method according to JIS K5600-5-6. The evaluation criteria were "A: Missing area is less than 10%, " "B: Missing area is 10% or more and less than 30%, " "C: Missing area is 30% or more and less than 50%, " "D: Missing area is 50% or more". The evaluation results are shown in Table 2.

[0052] [Table 2]

Claims

1. A water-based primer material comprising a synthetic resin emulsion and a pigment, The synthetic resin emulsion contains the following components constituting the synthetic resin: (a) a (meth)acrylic acid alkyl ester having an alicyclic hydrocarbon group, and (b) an alkoxysilane compound; Including, The synthetic resin contains the alkoxysilane compound (b) in an amount of 0.01 to 7% by mass, The water-based primer is characterized in that the glass transition temperature of the synthetic resin is 15°C or lower.

2. Furthermore, the synthetic resin emulsion contains, as a component constituting the synthetic resin, (c) containing an alkyl (meth)acrylate ester having an alkyl main chain with 1 to 2 carbon atoms in the alkyl portion, The water-based undercoat material according to claim 1, characterized in that the mass ratio [(a) / (c)] of the (a) (meth)acrylic acid alkyl ester having an alicyclic hydrocarbon group and the (c) (meth)acrylic acid alkyl ester having an alkyl main chain with 1 to 2 carbon atoms in the alkyl portion is 100 / 0 to 1 / 99.

Citation Information

Patent Citations

  • Designed coating film formation method

    JP2004122052A